THE DYNAMICS OF CARBON DIOXIDE SEQUESTRATION RELATED TO THE STOCKED STANDS OF TROPICAL FOREST IN CENTRAL KALIMANTAN - Junaedi, Ajun; Ludang, Yetrie; Hidayat, Nisfiatul (Acta Scientiae et Intellectus, 2024)
The purpose of the research is to measure the dynamics of biomass, carbon and CO2 sequestration related to the stocked stands with liberation and non-liberation treatment on the permanent sample plot of PT. Indexim Utama’s IUPHHK-HA year 2011 - 2015. The estimation of stocked stands biomass storage above and below ground biomass/roots used Brown’s allometric equation (1997) and Indonesian National Standard or SNI 7724 (2011). Meanwhile, the estimation of carbon storage and CO2 sequestration used the equation of SNI 7724 (2011) dan IPCC (2006). These dynamics are calculated by using Stock-Difference method (IPCC, 2006). The result of the observation shows the average biomass, carbon, and CO2 of the stocked stands with liberation treatment during 4 years were about 13.28 ton/ha/year; 6.24 tonC/ha/year; 22.91 tonCO2/ha/year. Meanwhile the biomass storage rate, carbon, and CO2 sequestration of the stocked stands observed with non-liberation treatment were about 10.75 ton/ha/years; 5.04 tonC/ha, and 18.49 tonCO2/ha/year.